Occurrence of Antibiotics in Aqueous Matrices: An Outlook about the Situation in Brazil - Lima, Karla V.L. [UNESP]; de Jesus, Jany H.F. [UNESP]; Nogueira, Raquel F.P. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2023)
This review presents data regarding the occurrence of antibiotics in several aqueous matrices in Brazil reported in the last twelve years (from 2010 to 2022). Despite limited research on the topic, Brazil has the highest number of published data on antibiotics in surface water (SW) among Latin American countries. However, these studies primarily focused on the southern and southeastern regions, providing an incomplete picture of antibiotic occurrence in the aquatic environment of the country. Data from 24 papers show the detection of 23 antibiotics in 5 aquatic matrices, including drinking water, ranging from 0.13 ng L-1 to 37.30 μg L−1. Occurrence in SW was the most reported, and sulfamethoxazole was the antibiotic most prevalent and concentrated in this matrix (7112.4 ng L-1). Besides the fact that antibiotics are only partially removed in sewage treatment plants, in Brazil, only 55.8% of the sewage generated is collected, and 80.8% of the collected sewage is treated, which aggravates the release of antibiotics to the aquatic environment. This poses a significant concern due to potential harm to non-target organisms and antibiotic-resistant bacteria proliferation, worsening global antimicrobial resistance. Given this scenario, regular monitoring to assess the presence of antibiotics and resistant bacteria is crucial, enabling timely interventions and appropriate mitigation measures.
Keywords: effluent; emerging contaminants; hospital wastewater; pharmaceuticals; surface water